The Discourse of Islam Nusantara in Indonesian Historiography (An Archaeology of Knowledge Approach) - Rahmah, Farida Novita; Mahamid, Mochammad Nginwanun Likullil (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The discourse of Islam Nusantara has emerged as a response to the growing Islamic conservatism and the rising influence of transnational Islam in the Reform Era. Nahdlatul Ulama (NU) promoted this concept as a strategy to preserve a religious expression that aligns with local culture and national values. This article aims to trace the development of the Islam Nusantara discourse using Michel Foucault’s archaeology of knowledge approach. This method not only examines the content of the discourse but also analyzes the historical and social conditions that made its emergence possible. The research was conducted using historical methods, including source collection, source criticism, interpretation, and historiography. Various sources such as NU congress documents, digital archives, and academic literature served as the main materials for analysis. The findings reveal that Islam Nusantara is not merely a religious concept but also a site of ideological dialectics between the preservation of tradition, the demands of modernity, and the dynamics of power. This article invites readers to view the discourse of Islam Nusantara as a continuously evolving social construct rather than a fixed and final entity.